2003
DOI: 10.1016/s0042-6989(03)00077-4
|View full text |Cite
|
Sign up to set email alerts
|

Motion coherence thresholds in infants––different tasks identify at least two distinct motion systems

Abstract: Optokinetic nystagmus (OKN) can be demonstrated from birth, but behavioural discrimination tasks such as habituation and preferential looking do not reveal any sensitivity to motion direction until a few weeks of age. This study compared coherence threshold for motion direction for OKN and preferential looking responses using closely comparable stimuli, in infants between 6 and 27 weeks of age. Infants were tested with two random dot motion displays, a uniform area of moving dots for OKN responses and a displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
1
38
1
Order By: Relevance
“…The experimenter used a variety of cues, including tracking movements, OKN, or fixation preference, to make her judgments, depending on what was most reliable for a given infant. Mason et al (2003) have reported that OKN measurements reveal earlier abilities and lower thresholds for global motion discrimination than traditional fixation preference measurements in human infants, and it might be that the early measurements based on OKN slightly overestimate motion sensitivity. Thus, the large variance of thresholds at this age could be due to the mixture of cues used by the observer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimenter used a variety of cues, including tracking movements, OKN, or fixation preference, to make her judgments, depending on what was most reliable for a given infant. Mason et al (2003) have reported that OKN measurements reveal earlier abilities and lower thresholds for global motion discrimination than traditional fixation preference measurements in human infants, and it might be that the early measurements based on OKN slightly overestimate motion sensitivity. Thus, the large variance of thresholds at this age could be due to the mixture of cues used by the observer.…”
Section: Discussionmentioning
confidence: 99%
“…Reflexive eye movements (OKN) to motion stimuli are identifiable in newborns (Volkman & Dobson, 1976;Atkinson, 1979;Naegele & Held, 1982;Mason et al, 2003). Psychophysical studies provide evidence for directional motion sensitivity within the first 3 months of life in humans (Braddick, 1993;Wattam-Bell, 1996;Dobkins & Teller, 1996;Banton et al, 2001; see Braddick et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants have been found to discriminate structure from motion random-dot displays by 7 months (Spitz, Stiles, & Siegel, 1993). At a more basic level of processing, the coherence threshold for the discrimination of a pattern made by moving dots is first measurable after approximately 3 months (Mason, Braddick, & Wattam-Bell, 2003;Banton, Dobkins, & Bertenthal, 2001;Banton, Bertenthal, & Seaks, 1999;Wattam-Bell, 1994). Fully adult performance appears to occur only in late childhood or early adolescence in both form and motion coherence tasks (Ellemberg, Lewis, Maurer, Brar, & Brent, 2002;Gunn et al, 2002;Lewis et al, 2002;Atkinson, 2000;Giaschi & Regan, 1997) as well as texture segmentation (Sireteanu & Rieth, 1992).…”
Section: Comparison To Previous Developmental Studies Of Global Integmentioning
confidence: 99%
“…In human and macaque infants perception of simple motion is present early after birth (Kiorpes and Movshon, 2004). Perception of coherent motion and pattern motion develops later, i.e., ϳ7 weeks of age and matures through the first year of life in humans Mason et al, 2003), and between 10 and 18 weeks in macaques (Hall-Haro and Kiorpes, 2008).…”
Section: Introductionmentioning
confidence: 99%